An assessment on the knowledge and attitudes of university students concerning adult immunization and COVID-19 vaccine in Turkey - Kerkez, Mujde; Capuk, Hueseyin (W B Saunders Co-Elsevier Inc, 2023)
There is ongoing concern about vaccine hesitancy amongst young adults in Turkey. In October 2021 just 53% of 18-25-year olds were fully vaccinated. This study aimed to assess the knowledge and attitudes of university students concerning adult immunization, COVID-19 vaccine, and COVID-19 vaccine literacy to better understand why it is difficult to encourage young adults to be vaccinated. This cross-sectional study was conducted with 307 university students that included socio-demographic characteristics, knowledge of adult immunization, attitudes toward COVID-19 vaccination, and vaccine literacy. The data were collected using a socio-demographic characteristics form, a knowledge form for adult immunization, the attitudes toward the COVID-19 vaccine scale, and the COVID-19 vaccine literacy scale. While more than half of the students (52.8%) had a low level of knowledge about adult immunization, half percent of the students (50.5%) stated that they did not know anything about adult vaccination. Twenty-six and half percent of the students stated that they weren't vaccinated because they were afraid of the side effects of the vaccines for adults. The difference between the student's level of knowledge about adult immunization and their mean scores on the attitudes toward the COVID-19 vaccine scale was not statistically significant (p > 0.05); whereas, the difference between their level of knowledge about adult immunization and their mean scores of the COVID-19 vaccine literacy scale was statistically significant (p < 0.05). There were low levels of vaccine literacy amongst Turkish university students and more than half of the students reported that they did not know and twenty-six percent of students (26 %) of the students were fearful of vaccine side effects. Students outside of the faculty of health had a low level of knowledge about vaccines. Examining and improving vaccine literacy amongst university students could lead to improved compliance with vaccination programs for both COVID-19 and other adult vaccines that are important for community health and well-being.
Keywords: Turkey; Adult immunization; COVID-19; Attitude; Vaccine literacy; Nurse